Impact of Periodontal Treatment and Demographic and Socioeconomic Factors on Tooth Loss in Persons with Disabilities: An Analysis of Korean National Health Insurance Claims Data - Bo-Ra Kim (The Korean Society of Dental Hygiene Science, 2023)
Background: This study aimed to analyze the effects of periodontal treatment and individual- and tooth-related factors on tooth extraction in people with disabilities.Methods: The Korea National Health Insurance claims data of individuals with disabilities aged 40∼64 years with chronic periodontitis in 2008 were obtained. Of these, data on the disabled who underwent scaling/root plaining, subgingival curettage/periodontal surgery, or non-periodontal treatments, and data on their teeth were selected. The extraction of 716,688 teeth from 39,097 patients was tracked until 2018, and the patient- and tooth-level factors related to tooth loss were identified using a mixed-effect logistic regression analysis. Results: Data from approximately 17% of the teeth were extracted during a follow-up period of approximately 11 years. Among the tooth-level variables, scaling/root planing treatment at baseline and periodontal treatment during the follow-up period were associated with a lower risk of tooth loss (odds ratio=0.692 and 0.769, respectively, p＜0.001). Non-vital teeth increased the risk of tooth loss by 3.159 times (p＜0.001). Among the patient-level variables, females were less likely to have lost their teeth than males, and those with orthopedic impairment or brain lesions/mental disabilities, a higher age group, lower income level, or residents in medium/small cities or rural areas were more likely to have lost their teeth (p＜0.001). Conclusion: Through approximately 11 years of follow-up, scaling or root planing, experience with periodontal treatment at least once, female sex, older age, lower income, smaller residential areas, type of disability, and pulp vitality were found to be associated with tooth loss in individuals with disabilities aged 40∼64 years with chronic periodontitis. To prevent tooth loss in individuals with disabilities, it is necessary to establish a dental treatment plan that considers the timing of periodontal treatment and the characteristics of the patient and teeth.